Organizational Family Values and Happiness in Nonprofit Organizations - Faletehan, Aun Falestien (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
Existing studies of individual retention in the nonprofit organizational setting seem relatively silent on the significance of corporate family values and personal happiness, although both concepts could improve particular commitment, better collaboration, and a propensity to perform pro-social behaviour. Grounded on 32 interviews from four Indonesian nonprofit organizations, this article develops the individual retention model based on organizational family values generated by management practices. The findings show that corporate family values would lead to personal happiness, resulting in personal retention. Meanwhile, nonprofits could influence personal satisfaction and retention by generating organizational family values through certain management practices. This model has broadened our understanding of the relations between corporate values, unique perspectives, and management practices; while also contributing to HRM practitioners in managing staff and volunteers.